2004
DOI: 10.1016/j.ymthe.2004.06.110
|View full text |Cite
|
Sign up to set email alerts
|

Differential Myocardial Gene Delivery by Recombinant Serotype-Specific Adeno-associated Viral Vectors

Abstract: Recombinant cross-packaging of adeno-associated virus (AAV) genome of one serotype into other AAV serotypes has the potential to optimize tissue-specific gene transduction and expression in the heart. To evaluate the role of AAV1 to 5 virion shells on AAV2 transgene transduction, we constructed hybrid vectors in which each serotype capsid coding domain was cloned into a common vector backbone containing AAV2 replication genes. Constructs were tested for expression in: (1) adult murine heart in vivo using direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 22 publications
3
53
1
Order By: Relevance
“…In contrast to the transient expression mediated by those vector systems, AAV vectors enable long-term gene expression in the heart of small and large animals. 5,16,24,37 Our study demonstrates that UTMD loaded with AAV-6 or -9 significantly increased cardiac reporter gene expression compared to systemic infusion of vectors without microbubbles in the presence of ultrasound. As the diagnostic ultrasound used in this study is not able to increase transduction itself, 34 the increased transduction efficiency in the microbubble group can be explained by high local vector concentration after destruction of AAV-loaded microbubbles in the cardiac capillaries and increased capillary permeability resulting from high velocity fluid microjets.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In contrast to the transient expression mediated by those vector systems, AAV vectors enable long-term gene expression in the heart of small and large animals. 5,16,24,37 Our study demonstrates that UTMD loaded with AAV-6 or -9 significantly increased cardiac reporter gene expression compared to systemic infusion of vectors without microbubbles in the presence of ultrasound. As the diagnostic ultrasound used in this study is not able to increase transduction itself, 34 the increased transduction efficiency in the microbubble group can be explained by high local vector concentration after destruction of AAV-loaded microbubbles in the cardiac capillaries and increased capillary permeability resulting from high velocity fluid microjets.…”
Section: Discussionmentioning
confidence: 67%
“…21 In comparison to AAV-2, AAV-6-pseudotyped vectors lead to higher myocardial transduction after intramyocardial injection and systemic administration. [22][23][24][25] Other AAV serotype vectors such as AAV-8 or -9 resulted in even higher cardiac transduction levels after intravenous injection in adult mice. [26][27][28] Specificity and efficiency of myocardial gene transfer with pseudotyped AAV vectors could be further increased using the 1.5 kb myosin light chain-2v promoter fused to a cytomegalovirus (CMV) enhancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant AAV (rAAV) provides a non-pathogenic and latent infection by integration into the host genome. It also demonstrated high transduction efficiency in both dividing and non-dividing cells with persistent transgene expression (19,20). The AAV2 gene delivery system is undergoing clinical trials (from phase I to phase III) in several hospitals in the United States and no obvious toxicity or side-effects have been reported (18,21).…”
Section: Introductionmentioning
confidence: 99%
“…Blankinship et al 77 reported that rAAV6 effectively transduced skeletal muscle. Du et al 78 reported that delivery genes to myocardial tissue may be enhanced by AAV serotype 1-specific vectors.…”
Section: Gene Delivery For Vascular Diseasesmentioning
confidence: 99%